2015
DOI: 10.1186/s13073-015-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

The Murray collection of pre-antibiotic era Enterobacteriacae: a unique research resource

Abstract: Studies of historical isolates inform on the evolution and emergence of important pathogens and phenotypes, including antimicrobial resistance. Crucial to studying antimicrobial resistance are isolates that predate the widespread clinical use of antimicrobials. The Murray collection of several hundred bacterial strains of pre-antibiotic era Enterobacteriaceae is an invaluable resource of historical strains from important pathogen groups. Studies performed on the Collection to date merely exemplify its potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The ancestor of the type 1 lineage that contains neither the ARI-A nor the ARI-B islands is still to be discovered. The Murray Collection of preantibiotic era strains recovered as early as 1917 was recently sequenced (Baker et al, 2015). Though it may have been a source of ancestral IncC plasmids, a search of the sequencing metadata showed that no IncC plasmids were detected in the collection.…”
Section: Distribution Of Gisul2mentioning
confidence: 99%
“…The ancestor of the type 1 lineage that contains neither the ARI-A nor the ARI-B islands is still to be discovered. The Murray Collection of preantibiotic era strains recovered as early as 1917 was recently sequenced (Baker et al, 2015). Though it may have been a source of ancestral IncC plasmids, a search of the sequencing metadata showed that no IncC plasmids were detected in the collection.…”
Section: Distribution Of Gisul2mentioning
confidence: 99%
“…Historical collections of bacteria provide us with relevant data from the pre-antibiotic period (Baker et al, 2014(Baker et al, , 2015Devault et al, 2014). Our historical isolates were collected from 1969 to 1970 during the antibiotics classic golden age, but they had not been exposed to newly discovered antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these growing repositories, one of the most studied historical bacterial collections is the Murray Collection. The Murray Collection comprises several hundred Enterobacteriaceae strains collected in the preantibiotic era (1917 to 1954) from a wide range of geographic areas (32). This now-public collection, held by the NCTC, provides a unique genomic resource to provide insight into an era before the routine use of antibiotics and so is particularly useful for studies investigating the evolution and accumulation of AMR.…”
Section: The Collectionsmentioning
confidence: 99%